Kajian Strategi Pengembangan Objek Wisata Puncak Bulotalangi (Bumi Cerah) Dengan Metode Analisis SWOT Kabupaten Bone Bolango - Yusuf, Daud; Nusi, Wirdawati; Maryati, Sri (Universitas Pahlawan Tuanku Tambusai, 2024)
The Puncak Bulotalangi (Bumi Cerah) tourism object in Bone Bolango Regency has great natural tourism potential, but faces several challenges, such as low accessibility and inadequate facilities. This study aims to formulate a tourism development strategy using the SWOT analysis method, which includes identifying strengths, weaknesses, opportunities, and threats. The research method used is qualitative descriptive through observation, interviews, and documentation. The results of the study indicate that this tourism objeet is in quadrant IV of the SWOT matrix, which indicates Weakness-Threat (WT) conditions. A defensive strategy is needed to minimize weaknesses, such as damaged road access and reduce external threats, in the form of competition with other tourist attractions. infrastructure development and increased promotion are very important to increase the attractiveness and number of visitors to Puncak Bulotalangi.